Peritoneal Dialysis–Related Peritonitis due to Coagulase-Negative Staphylococcus - Carlos Henrique Camargo; Maria de Lourdes Ribeiro de Souza da Cunha; Jacqueline Costa Teixeira Caramori; Alessandro Lia Mondelli; Augusto Cézar Montelli; Pasqual Barretti (2014)
Coagulase-negative Staphylococcus (CNS) is the most frequent cause of peritoneal dialysis (PD)-related peritonitis in many centers. This study aimed to describe clinical and microbiologic characteristics of 115 CNS episodes and to determine factors influencing the outcome.This study reviewed the records of 115 CNS peritonitis episodes that occurred in 74 patients between 1994 and 2011 at a single university center. Peritonitis incidences were calculated for three consecutive 6-year periods (P1, 1994-1999; P2, 2000-2005; P3, 2006-2011) and annually. The production of biofilms, enzymes, and toxins was evaluated. Oxacillin resistance was evaluated based on its minimum inhibitory concentration and the presence of the mecA gene.The overall incidence of CNS peritonitis was 0.15 episodes per patient per year and did not vary over time (0.12, 0.14, and 0.16 for P1, P2, and P3, respectively; P=0.21). The oxacillin resistance rate was 69.6%. Toxin and enzyme production was infrequent and 36.5% of CNS strains presented the gene encoding biofilm production. The presence of icaAD genes associated with biofilm production was predictive of relapses or repeat episodes (odds ratio [OR], 2.82; 95% confidence interval [95% CI], 1.11 to 7.19; P=0.03). Overall, 70 episodes (60.9%) resolved; oxacillin susceptibility (OR, 4.41; 95% CI, 1.48 to 13.17; P=0.01) and vancomycin use as the first treatment (OR, 22.27; 95% CI, 6.16 to 80.53; P<0.001) were the only independent predictors of resolution.Oxacillin resistance and vancomycin use as the first treatment strongly influence the resolution rate in CNS peritonitis, which reinforces the validity of the International Society for Peritoneal Dialysis guidelines on monitoring bacterial resistance to define protocols for initial treatment. These results also suggest that the presence of biofilm is a potential cause of repeat peritonitis episodes.